2022
DOI: 10.1016/j.nicl.2021.102907
|View full text |Cite
|
Sign up to set email alerts
|

Angular gyrus connectivity at alpha and beta oscillations is reduced during tonic pain – Differential effect of eye state

Abstract: Highlights Tonic pain differentially altered AG connectivity during eyes closed and eyes open. Negative mood and/or sleep quality can influence pain-related connectivity. Eyes closed baseline may allow for a reliable detection of pain-related changes. Eyes-closed-eyes-open sequence is crucial for assessing pain-related connectivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 84 publications
1
13
0
Order By: Relevance
“…Therefore, this study investigated how the DMN connectivity at alpha (but not beta) contributes to peak pain intensity. Additionally, our previous work (Alhajri et al, 2022b) along with other findings (Klimesch et al, 2006; Nir et al, 2012) have also shown that lower alpha (8–10 Hz) may be more involved in pain perception than upper alpha (11–13 Hz) oscillations. Therefore, the contribution of pain‐free DMN connectivity to pain intensity was examined at lower alpha (8–10 Hz).…”
Section: Methodssupporting
confidence: 61%
See 2 more Smart Citations
“…Therefore, this study investigated how the DMN connectivity at alpha (but not beta) contributes to peak pain intensity. Additionally, our previous work (Alhajri et al, 2022b) along with other findings (Klimesch et al, 2006; Nir et al, 2012) have also shown that lower alpha (8–10 Hz) may be more involved in pain perception than upper alpha (11–13 Hz) oscillations. Therefore, the contribution of pain‐free DMN connectivity to pain intensity was examined at lower alpha (8–10 Hz).…”
Section: Methodssupporting
confidence: 61%
“…Using a discrete multiple source method (Scherg et al, 2019), EEG data were transformed in BESA to source space, and pre‐defined resting‐state source montages for the DMN were used focusing on four regions: mPFC, PCC, right and left angular gyrus (rAG and lAG) (Alhajri et al, 2022b). The locations of the DMN areas were determined by Montreal Neurological Institution based on the DMN system described by Power et al (Power et al, 2011).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another interesting aspect of the AG in the process of sensemaking is the ability to integrate multimodal information. One can draw parallels with a similar AG role in the subjective nature of pain perception (Alhajri et al, 2021), as pain processing also depends on the integration of complex sensory, cognitive and emotional aspects in a personalized and contextdependent manner.…”
Section: Section 6: Outstanding Questions For Future Researchmentioning
confidence: 91%
“…As with Study I and II, the sensory-motor interaction between electrical stimuli and MVF-induced illusory movements investigated in Study III was related to the underlying neurophysiological oscillatory mechanism at the alpha frequency (alpha ERD/ERS), an EEG rhythm acknowledged for its role in motor and sensorynociceptive processes 89,120,123 as well as for its functional meaning within the core structures of the triple network (ECN, DMN, and SN) [239][240][241] . In Study III, the alpha ERD in the frontoparietal cortical areas reflects the activation of the executive efferent motor outputs enacted to interfere with the concomitant afferent sensory inputs.…”
Section: Role Of Attentional Triple Network In Pain Modulationmentioning
confidence: 87%